Desempenho e morfometria da mucosa de duodeno de frangos de corte alimentados com farelo de canola, durante o período inicial - Figueiredo, Denise Fontana [UNESP]; Murakami, Alice Eiko; Dos Santos Pereira, Marli Aparecida; Furlan, Antonio Claudio; Toral, Fábio Luiz Buranelo [UNESP] (FapUNIFESP (SciELO), 2003)
A trial was carried to verify the effect of increasing levels (0, 10, 20, 30 and 40%) of canola meal in diets of broiler chickens on performance and mucous morphology, during the starting period (1 - 21 days). One thousand 1-d male chicks were assigned to a randomized experimental assay, with five treatments, four replicates and 50 birds per experimental unit. At the 1 st, 21 st and 41 st days, the birds and the rations were weighed. At the 21 st day, two birds of each experimental unit were sacrificed for collection of a duodenum segment to evaluate the intestinal morphometry. The results demonstrated that increasing levels of canola meal resulted in linear reduction on weight gain, weight and feed intake and worst feed conversion. During the growing period (21 to 41 days), when all birds received similar diet, average weight and weight gain decreased, as the canola meal levels increased, while feed conversion and feed intake were similar. Data regarding mucous morphology, submitted to the regression analysis, demonstrated that the crypt depth increased, as the canola meal levels increased. It is possible to include up to 20% of canola meal without damages on broiler performance and digestive tract.
Performance and duodenum mucous morphometry of broiler chickens fed canola meal, during the starting period
Keywords: Anti-nutritional factor; Crypt depth; Duodenum; Tannin; Villi height; Aves; Brassica napus var. napus; Gallus gallus; Sinapis arvensis